Bittersweet : [large type] how sorrow and longing make us whole - Cain, Susan (Random House Large Print, 2022)
"With Quiet, Susan Cain urged our society to cultivate space for the undervalued, indispensable introverts among us, thereby revealing an untapped power hidden in plain sight. Now she employs the same mix of research, storytelling, and memoir to explore why we experience sorrow and longing, and how embracing the bittersweetness at the heart of life is the true path to creativity, connection, and transcendence. Cain shows how a bittersweet state of mind is the quiet force that helps us transcend our personal and collective pain. If we don't acknowledge our own heartache, she says, we can end up inflicting it on others via abuse, domination, or neglect. But if we realize that all humans know--or will know--loss and suffering, we can turn toward one another"--